Analysis of Factors Affecting Inflation in Indonesia during The Covid-19 Pandemic: Analysis of Factors Affecting Inflation in Indonesia during The Covid-19 Pandemic - Dara Septika Natalia Anggraeni (Jurnal Forum Analisis Statistik, 2022)
The Covid-19 pandemic that hit the world today impacts various community activities in Indonesia, one of which is household consumption related to the price of goods/services. One indicator that can describe information about price changes in a region is to look at the development of inflation, where inflation is calculated from the Consumer Price Index (CPI) figures. Therefore, this study aims to determine the picture of Indonesian people's spending patterns through CPI spending groups and which dominant variables affect inflation during this pandemic. This study focused on the CPI of 90 cities in Indonesia in March 2020-August 2021 based on the Commodity Cost of Living Survey (SBH) 2018, using a literature review supported by quantitative descriptive analysis and factor analysis of secondary data. This study showed that the personal care and services group was the spending group that always occupied the top CPI position. In contrast, the information, communication, and financial services expenditure group rank lowest compared to other spending groups. As for the factor analysis results, of the 16 variables obtained, five factors can explain the variation of 58.833 percent against inflation.